Effect of the level of technology of dairy farms in the province of Lima on the compositional, hygienic and sanitary quality of milk - Sandoval-Monzón, Rocio (2023)
The aim of this study was to establish the relationship between the level of technology and the quality of milk in dairy farms in the province of Lima, Peru. The study was carried out in 18 farms. Data was collected through surveys, as well as analysis of milk samples collected during three consecutive days. Variables related to the level of technology of the farms, as well as the physical, compositional, hygienic and sanitary quality of the milk were evaluated. The results revealed average technical scores of 7.1/10 in management, 4.3/10 in facilities and resources, 4.2/6 in milking, and 15.6/26 in the global technification. Regarding the quality of the milk, average temperatures of 18.38 °C, pH of 6.60, average density of 1.030 g/mL, total solids of 12.11%, and fat of 3.46% were recorded. The mean count of mesophilic bacteria was 210x106, coliforms 6x107, and somatic cells 300x105 cells/mL. Significant negative correlations were found between the level of technology with the storage temperature, the sedimentation score, and the count of mesophilic and coliform bacteria in the milk. In addition, it was evident that farms with better level of technology presented significantly better milk quality parameters compared to those with less technology.